Computational gas-solids flows and reacting systems theory, methods and practice - Pannala, Sreekanth, 1971-; Syamlal, Madhava; O'Brien, Thomas J. 1941- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book provides various approaches to computational gas-solids flow and will aid the researchers, graduate students and practicing engineers in this rapidly expanding area"--Provided by publisher.
Keywords: Two-phase flow.; Gas-solid interfaces.; Computational fluid dynamics.; elektronické knihy; electronic books